Quality Control Analysis of Instant Tea Packaging Using the FMEA Method at PT Respati Kemasindah: Analisis Pengendalian Kualitas Kemasan Teh Instan Menggunakan Metode FMEA di PT Respati Kemasindah - Saeful Imam; Suci Puji Lestari (JRST (Jurnal Riset Sains dan Teknologi), 2026)
PT Respati Kemasindah is a company engaged in the conversion of flexible packaging using rotogravure printing technology, including the production of instant tea packaging. The defect rate of instant tea packaging in the production process reaches 8.48%, which exceeds the company’s tolerance limit of 3%, indicating deficiencies in quality control. This study aims to analyze potential failures occurring in the instant tea packaging production process and to determine improvement priorities to reduce the defect rate. Failure Mode and Effects Analysis (FMEA) is employed by calculating the Risk Priority Number (RPN) based on severity, occurrence, and detection parameters. The results indicate that dry lamination defects have the highest RPN value of 155, followed by misprint defects and uneven printing. Based on these findings, improvement strategies are proposed with a focus on enhancing machine maintenance effectiveness, ensuring consistent implementation of standard operating procedures (SOPs), and improving operator competence and working conditions. This study is expected to serve as a fundamental reference for decision-making in improving quality control effectiveness and reducing the defect rate of instant tea packaging.   ABSTRAK (Bahasa Indonesia) PT Respati Kemasindah merupakan perusahaan di bidang converting kemasan fleksibel berbasis cetak rotogravure, salah satunya yaitu kemasan teh instan. Persentase kecacatan kemasan teh instan sebesar 8,48% dalam proses produksi kemasan yang melampaui batas toleransi perusahaan sebesar 3%, mengindikasikan adanya permasalahan dalam pengendalian kualitas.  Penelitian ini bertujuan untuk menganalisis potensi kegagalan yang terjadi dalam proses produksi kemasan teh instan serta menentukan prioritas perbaikan guna menurunkan tingkat kecacatan produk. Metode yang digunakan adalah Failure Mode and Effects Analysis (FMEA) dengan menghitung nilai Risk Priority Number (RPN) berdasarkan parameter severity, occurrence, dan detection. Hasil penelitian menunjukkan bahwa cacat dry laminasi memiliki nilai RPN tertinggi sebesar 155, diikuti oleh cacat misprint, dan unsmooth printing. Berdasarkan hasil tersebut, usulan perbaikan difokuskan pada peningkatan efektivitas pemeliharaan mesin, penegakan konsistensi penerapan SOP, serta peningkatan kompetensi dan kondisi kerja operator. Penelitian ini diharapkan dapat menjadi acuan dasar pengambilan keputusan dalam meningkatkan efektivitas pengendalian kualitas dan menurunkan tingkat kecacatan kemasan teh instan.